Fe-single-atom catalyst anchored on N,S-codoped carbon derived from Fe(II) complexes with three bidentate precursors for superior oxygen reduction performance - Yining Liang; Yue Yang; Lin Xu; Tianping Wang; Gengzhe Shen; Jing Kong; De Ning; Zhengjian Chen (Next Materials, 2025)
Constructing single-atom active sites for high catalytic performance remains a significant challenge due to their easy migration and agglomeration. In this study, we constructed a noble-metal-free catalyst (Fe@NPDSBPC) derived from three precursors with strong N,N or S,S-bidentate chelating abilities, effectively coordinating and anchoring Fe2 + ions during pyrolysis to form single Fe sites dispersed on N,S-codoped porous carbon. The synergistic coordination of the three precursors endowed Fe@NPDSBPC with hierarchical porous structures, a high specific surface area (505 m2 g−1) and a high N,S-codoping content (9.83 at%) compared to other carbon products (≤ 327 m2 g−1 and 7.37 at%, respectively) prepared from any two of the three precursors. Fe@NPDSBPC demonstrated excellent oxygen reduction performance with a significantly higher half-wave potential (0.924 V), kinetic current density at 0.85 V (40.0 mA cm−2) and electrochemical active surface area (365 cm2ECSA) and significantly better durability and methanol tolerance than the benchmark Pt/C catalyst (0.882 V, 13.3 mA cm−2 and 159 cm2ECSA, respectively). When used in zinc-air batteries, Fe@NPDSBPC achieved considerably higher power density (210 mW cm−2), specific capacity (767 mAh gzn−1), and longer-term cycling durability (200 h) at 5 mA cm−2 than Pt/C (148 mW cm−2, 613 mAh gzn−1 and 55 h, respectively).